Sukarno dan Pembangunan Stadion Gelora Bung Karno di Senayan, 1959-1962 - Muhammad Rizaldy (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
The building of Gelora Bung Karno stadium was based on Indonesia requirement to become host of Asian Games IV on 1962. The needs for a multi-sports event and Sukarno vision to build Jakarta as “mercusuar” or lighthouse for new emerging forces has affected the expansion of building in Jakarta to meet the need. Hotel Indonesia, statues and monuments, are built for this purpose. In regards to Gelora Bung Karno stadium, the areas that has been chose was Senayan, that was still a rural, and farming area. People who lived there are moved and relocated to Tebet. Pembangunan stadion Gelora Bung Karno didasari oleh keinginan Indonesia untuk menjadi tuan rumah Asian Games IV pada tahun 1962. Kebutuhan untuk pesta olahraga dan keinginan Sukarno yang ingin menjadikan Jakarta sebagai mercusuar negara-negara berkembang telah menyebabkan terjadinya ledakan pembangunan untuk memenuhi kepentingan tersebut. Pembangunan Hotel Indonesia, patung-patung, dan monumen, dimaksudkan untuk memenuhi kepentingan ini. Dalam pembangunan Stadion Gelora Bung Karno, wilayah yang ditunjuk untuk dijadikan lokasi pembangunan adalah kawasan Senayan, yang masih berupa daerah-daerah perkebunan, serta juga terdapat pemukiman warga, Soekarno menunjuk wilayah kampung Senayan untuk pembangunan Stadion Gelora